2023
DOI: 10.3390/cells12242794
|View full text |Cite
|
Sign up to set email alerts
|

Functions of RNA-Binding Proteins in Cardiovascular Disease

Grégoire Ruffenach,
Lejla Medzikovic,
Wasila Sun
et al.

Abstract: Gene expression is under tight regulation from the chromatin structure that regulates gene accessibility by the transcription machinery to protein degradation. At the transcript level, this regulation falls on RNA-binding proteins (RBPs). RBPs are a large and diverse class of proteins involved in all aspects of a transcript’s lifecycle: splicing and maturation, localization, stability, and translation. In the past few years, our understanding of the role of RBPs in cardiovascular diseases has expanded. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Loss or the dysregulated activity of several RBPs have been closely associated with cardiomyopathies in humans or in animal models, as exemplified by RBM20 mutations in DCM patients [ 13 ]. With the expanded identification of the cardiac-specific RBPome, the contribution of RBP-mediated post-transcriptional regulation of cardiac-specific gene expression networks has gained considerable interest for better understanding the complexity of heart development and function [ 22 , 23 , 24 , 25 , 26 ]. Importantly, correcting pathogenic mutations in RBPs or manipulating their activity has the strong potential to rescue cardiomyopathy or promote cardiac regeneration after myocardial injury [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Loss or the dysregulated activity of several RBPs have been closely associated with cardiomyopathies in humans or in animal models, as exemplified by RBM20 mutations in DCM patients [ 13 ]. With the expanded identification of the cardiac-specific RBPome, the contribution of RBP-mediated post-transcriptional regulation of cardiac-specific gene expression networks has gained considerable interest for better understanding the complexity of heart development and function [ 22 , 23 , 24 , 25 , 26 ]. Importantly, correcting pathogenic mutations in RBPs or manipulating their activity has the strong potential to rescue cardiomyopathy or promote cardiac regeneration after myocardial injury [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in HuR expression in mouse cardiomyocytes has been observed during ischemia and reperfusion injury, where it has been shown to stabilize beclin mRNA, which leads to increased cell death. 7 Therefore, the role of HuR in cardiomyocyte and endothelial cell function in the context of cardiac fibrosis requires further investigation. Also, inflammation and cardiac tissue injury are closely associated, and previous studies have reported that HuR can up-regulate the expression of proinflammatory cytokines, including tumor necrosis factor α, 8 and increase the recruitment of macrophages in the injured heart.…”
mentioning
confidence: 99%